287 Citizen responders are an important supportive resource for relatives to cardiac arrest patients during resuscitation. (1st May 2022) - Kragh, AR; Andelius, L; Gregers, MCT; Zinckernagel, L; Christensen, AK; Folke, F; Thørnhøj-Thomsen, T; Hansen, CM
Abstract : Background: In Denmark, a volunteer responder (VR) system was implemented in 2017 1 . This study explored how volunteer responders provide emotional support for relatives to out-of-hospital cardiac arrest (OHCA) patients and how their presence during resuscitation is experienced by the relatives. Method: In-depth, semi-structured interviews were conducted with thirteen participants (four relatives and nine VRs) and analysed using thematic analysis. The analysis of data was an inductive process inspired by a hermeneutical interpretative approach. We indexed our data through the application of codes generated to draw out meaning from the text. Themes were created Following the analytical guide suggested by Braun and Clarke. Results: Eight themes emerged from the interviews: 'Acting to help – an inner calling', ' Citizen responders' cooperation and capability of organizing tasks', 'Taking care of relatives – a task equal with the resuscitation effort', 'Thoughts in the aftermath of the event', 'The feeling of being part of another family's history', 'The immediate relief when citizen responders arrive', 'mutual trust' and 'Citizen responders are strangers, yet rescue heroes'. Relatives experienced VRs as competent and skilled, and described a relationship based on mutual trust and confidence. VRs considered provision of emotional support for relatives as a natural calling equally significant with providing cardio-pulmonal resuscitation. Conclusion: Relatives to OHCA patients highly value volunteer responders' provision of emotional support during resuscitation. Volunteer responders consider provision of psychological support to relatives of equal importance to providing cardiopulmonary resuscitation when dispatched to OHCA. References: Andelius L, Malta Hansen C, Lippert FK, Karlsson L, Torp-Pedersen C, Kjær Ersbøll A, et al . Smartphone Activation of Citizen Responders to Facilitate Defibrillation in Out-of-Hospital Cardiac Arrest. Journal of the American College of Cardiology 2020;76 :43–53. https://doi.org/10.1016/j.jacc.2020.04.073. Conflict of interest: None. Funding: Astrid Rolin Kragh has received research grants from TrygFonden and Helsefonden.